2022
DOI: 10.1177/11769351221112457
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Treatment Data in Central Cancer Registries: When Are Supplemental Data Needed?

Abstract: Background: We evaluated treatment concordance between the Colorado All Payer Claims Database (APCD) and the Colorado Central Cancer Registry (CCCR) to explore whether APCDs can augment registry data. We compare treatment concordance for breast cancer, an extensively studied site with an inpatient reporting source and select leukemias that are often diagnosed outpatient. Methods: We analyzed concordance by cancer type and treatment, patient demographics, reporting source, and health insurance, calculating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…For this study, in breast cancer, we found higher concordance between SACT and HES-APC than reported by a previous study in colon cancer [8]. Several studies carried out in the United States comparing records across registry and claims data also found the combination of sources to be of value in identifying treatment use, noting registry data were more likely to have incomplete capture for older patients [22][23][24][25].…”
Section: Discussionsupporting
confidence: 45%
“…For this study, in breast cancer, we found higher concordance between SACT and HES-APC than reported by a previous study in colon cancer [8]. Several studies carried out in the United States comparing records across registry and claims data also found the combination of sources to be of value in identifying treatment use, noting registry data were more likely to have incomplete capture for older patients [22][23][24][25].…”
Section: Discussionsupporting
confidence: 45%
“… 27 Thus, Medicaid managed care is not likely to affect completeness of claims in Colorado. 20 In addition, our sample selection criteria omitted women who did not receive surgery, biasing the sample toward a treated group. However, only a small and statistically insignificant difference in surgical treatment was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Assessments of validity concluded that the linked data were of high quality 27 and APCD data on treatment and insurance status were reliable. 20 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient data are nearly complete on variables, such as race and ethnicity, and offer granular classifications 16 . However, treatment data are incomplete in registries, especially beyond the first course of treatment, 16 and can systematically vary by region, cancer site, insurance payer, and reporting source 17 . Because registries are population-based, linkages between APCDs and registries allow for assessments of people missing in APCDs.…”
mentioning
confidence: 99%